2020
DOI: 10.3390/s20082210
|View full text |Cite
|
Sign up to set email alerts
|

Visual Feedback Control of a Rat Ankle Angle Using a Wirelessly Powered Two-Channel Neurostimulator

Abstract: Peripheral nerve disconnections cause severe muscle atrophy and consequently, paralysis of limbs. Reinnervation of denervated muscle by transplanting motor neurons and applying Functional Electrical Stimulation (FES) onto peripheral nerves is an important procedure for preventing irreversible degeneration of muscle tissues. After the reinnervation of denervated muscles, multiple peripheral nerves should be stimulated independently to control joint motion and reconstruct functional movements of limbs by the FES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…In previous studies, neurostimulators used in healthy rat limbs showed step responses of 200–250 ms [ 14 , 15 ]. The denervated muscle reinnervated by stem cell transplantation in the present study had a similar response, and there was little oscillation generation and good precision of control in the visual feedback control tracking of the randomly moving target, as shown in the Supplementary Video S1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, neurostimulators used in healthy rat limbs showed step responses of 200–250 ms [ 14 , 15 ]. The denervated muscle reinnervated by stem cell transplantation in the present study had a similar response, and there was little oscillation generation and good precision of control in the visual feedback control tracking of the randomly moving target, as shown in the Supplementary Video S1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the FES strategy for drop foot reported in the paper had limitations, namely: the risk of infection by wires, the difficulty of selective stimulation of nerves, the need for manual manipulation, the impossibility of complex movements, and the inability to modulate stimulation incrementally. To overcome these challenges, our researchers developed a wirelessly powered two-channel neurostimulator that modulates switching according to the frequency of the transmitted signal and the controlled angle of the naive ankle joint by changing the stimulation electrode and current using a visual feedback control system based on the proportional–integral (PI) control method [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a wirelessly powered four-channel neurostimulator was developed to conduct FES for four nerves in a rat selectively to generate ankle and knee motions, as shown in Figure 1 : the tibial and peroneal nerves were related to ankle joint motion and the femoral nerve and branch of sciatic nerve connected to femoral biceps were related to knee joint motion. A magnetic resonance method [ 24 , 25 ] was employed to conduct wireless powering to the neurostimulator, which was developed based on our previous study [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we developed a four-channel wirelessly powered neurostimulator to control two joints in a rat: ankle and knee joints. The device we developed in this study has about 40 times higher resolution of stimulation current (from 0 to 0.4 mA with 0.1 A resolution) compared with our previous study [ 21 ], the stimulation frequency is controllable from 0 to 1 kHz, and duration is also controllable from 0 to 1 ms. The proposed method is a new strategy to reconstruct functional motion using their own hands or legs like robotic prostheses [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation